Effect of pH on the characteristics of electroless Ni-P coatings - Czagany M.; Baumli P. (Journal of Mining and Metallurgy. Section B: Metallurgy)
In this study electroless Ni-P coatings were deposited on W302 steel substrates. The effects of bath pH and heat treatment at 400°C were investigated on the surface morphology, phase structure, phosphorus content, thickness and microhardness of the coatings. It was observed that both the phosphorus content and coating thickness are dependent on the bath pH. In an acidic/neutral bath, low and medium phosphorus coatings with thickness of 13.9-19.8 μm were synthesized, while in an alkaline bath, high phosphorus, 4.8-5.8 μm-thick coatings were formed. Coatings containing medium or high P seemed to be amorphous, while low P coatings had microcrystalline structures. Hardness was also dependent on the composition of the coating. After heat treatment, the structure of the coatings transformed into crystalline Ni with the precipitation of Ni3P phases, which resulted further increases in hardness.